A Case Study on Effective Management of Abhayantra Arsha by Kshara Karma (International Journal of Ayurveda and Pharma Research, 2021)
Arshas being the most common grievous ailment and one of the eight most intractable disorders (Ashta Mahagada) explicited by Acharya Susruta & Vagbhata. Haemorrhoids are the dilatation of the anal and perianal venous plexus. The disturbance of Jatharagni is the most accepted cause of ano rectal problems, which further contributes to constipation. Constipation increases the back pressure into the haemorrhoidal veins to produce piles. Arsha requires a surgical technique in modern treatment, such as haemorrhoidectomy, rubber band ligation, and so on. Kshara is a caustic chemical, alkaline in nature, derived from medicinal plant ashes. The effect of Kshara karma is highly commended, it can replace the Shastra karma as it does the functions of Chedana, Bhedana, Lekhana karmas without using Shastras. Kshara karma can be utilised efficiently in individuals who are afraid of surgery as a complement for surgical operations. A 48years-old male patient presented with complaints of some mass coming out during defecation and bleeding while passing stool to the anorectal unit, OPD, National Institute of Ayurveda, deemed to be university Jaipur Rajasthan. The patient was treated successfully with Kshara karma application. The pile mass and per rectal haemorrhage was gone in 8 days and the patient was free of all symptoms within 18-20 days. The findings revealed that there are maximum advantages which are shared in this case study.